Matching violins in terms of timbral features - Łukasik, Ewa (Archives of Acoustics, 2006)
In the paper an attempt to match musical instruments in terms of timbral features of theirsound is made for a collection of 53 high quality concert violins. The starting point of theanalysis is calculation of a set of features based on harmonic analysis, e.g. odd-to-even harmonicsamplitudes ratio, intensity of the first and higher harmonics etc., and a set of linguisticdescriptors of violin timbre related to these features. The semantically disjoint categories oftimbre characteristics are considered. The result of the analysis is the allocation of instrumentsto those semantic categories with the expectation of the discovery of their similarities in individualtimbre dimensions. Although evident matching did not occur, certain possibilitiesof uncovering expert preferences have been noticed. The outcome of the research providessupportive cue for the design of a method of inferring preference models from the objectivecharacteristics of musical sounds.